Critical thinking on strengthening the NGO contribution to improve solidarity in public health. (13th November 2019) - Aslan, D
Abstract: Issue/background: Public health values transdisciplinary, multidisciplinary, and interdisciplinary perspectives. This background always advocates solidarity which usually finds its positive reflections in the society with the support of many institutional bodies including Non-governmental organization (NGO) movements. which move up solidarity. Globally, NGOs are represented by societies and associations. Turkey is one of the countries which NGO movement is frequent. Turkish NGOs in (public) health may vary on their vision(s) and mission(s). Such variety seems to be "good"; thus, complexity and duplications may occur when a strong systematic ground is not provided. In this paper, a systematic on the functionality of NGOs will be proposed to make the NGO movement more inclusive, accessible, transparent, and auditable in order to support solidarity using the experience of a local case. Results: The number of the societies is high in Turkey and they have a wide range of working area including health. Officially they are recorded in the Turkish Ministry of Internal Affairs (MoIA) and can be accessed via the website of the MoIA. There are about 300 000 societies which 116 000 of them are active. The majority of them are founded in big cities. Societies working on health focuses on different areas including professionalism, prevention, rehabilitation, etc. Such varieties may have the potential to create difficulty to follow up their work in a systematic manner. Lessons: As NGO/civil society movement is crucial for public health, the proposed steps may contribute to improve/support solidarity on any advocative work on health: To maintain transparency, and auditability To develop methods to prevent duplicative work To develop accessible "common" platforms to share experiences To improve adaptation capacity in the face of new requirements To improve networking among NGOs To improve the global perspective as well as the local one Key messages: Solidarity in public health can be achieved with the help of systematic and powerful NGO/civil society movement. Global needs and changes influence civil society dynamics and NGOs should be open to be updated in the face of new requirements.